2004
DOI: 10.1557/proc-848-ff9.2
|View full text |Cite
|
Sign up to set email alerts
|

Formation Mechanisms of Perovskite Pb(Ni1/3Nb2/3)O3 in Reaction-sintering Process

Abstract: Formation mechanisms of perovskite Pb(Ni 1/3 Nb 2/3 )O 3 (PNN) in the reaction-sintering process were investigated. Only the reflections of raw materials were detected at 400 o C. For pellets heated to 500 o C, pyrochlore phase Pb 2 Nb 2 O 7 (P 2 N 2 ) are found. Cubic Pb 3 Nb 4 O 13 (P 3 N 4 ) pyrochlore phase formed and became the main phase in pellets heated to 600 o C. After being heated to 800 o C, Pb 3 Nb 2 O 8 (P 3 N 2 ) pyrochlore phase formed in the pellets. As the pellets were heated to 900 o C, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Chen et al [21] have reported that the pyrochlore phase formed at 580 1C corresponds to the cubic pyrochlore Pb 3 Nb 4 O 13 . Liou et al [15] also reported the formation of cubic pyrochlore at 600 1C. The present analysis revealed a gradual change from 600 1C to 1000 1C, indicating that perovskite phase formation takes place throughout this temperature range and it is completed at around 1000 1C [16].…”
Section: Partial Covering Methods and Modulated Heatingsynthesis Of Pmsupporting
confidence: 52%
See 1 more Smart Citation
“…Chen et al [21] have reported that the pyrochlore phase formed at 580 1C corresponds to the cubic pyrochlore Pb 3 Nb 4 O 13 . Liou et al [15] also reported the formation of cubic pyrochlore at 600 1C. The present analysis revealed a gradual change from 600 1C to 1000 1C, indicating that perovskite phase formation takes place throughout this temperature range and it is completed at around 1000 1C [16].…”
Section: Partial Covering Methods and Modulated Heatingsynthesis Of Pmsupporting
confidence: 52%
“…The pyrochlore phase is very stable and if present with the perovskite phase, it affects the quality of PMN-PT [13]. Liou et al [14] reported that the cubic Pb 3 Nb 4 O 13 (P 3 N 4 ) pyrochlore phase appeared at 600 1C, whereas the perovskite phase was formed between 900 1C and 950 1C [15]. The fact that the bonding strength of oxygen and cations in the pyrochlore is stronger than that in the perovskite, and its formation temperature (450-600 1C) is much below that of perovskite (850-1050 1C) [16], imposed the major hindrance in the synthesis of PMN-PT [17].…”
Section: Introductionmentioning
confidence: 99%